(untitled) (Anclajes, 2025)
Las bestias (Ronaldo Menéndez, 2006) and Animal Tropical (Pedro Juan Gutiérrez, 2001) are examples of contemporary Cuban narrative where the animal presence shows prominence: in both works, the animal condition is key to the construction of the plot and the conformation of the human condition. This article analyzes how these notions are coherently integrated into the stories, and how the animal is imagined from what criticism describes as a strategic place in the discursive construction of human specificity. The analysis employs borrows from theories such as Jacques Derrida’s notion of human/animal division, Giorgio Agamben’s concept of anthropogenesis, and Gilles Deleuze and Félix Guattari’s assemblages.